PENGARUH PENAMBAHAN pH BUFFER-EKSTRAK KUNYIT, EKSRAK DAUN ASAM DAN KOMBINASI EKSTRAK KUNYIT – DAUN ASAM (Curcuma domestica Val. - Tamarindus indicia L.) TERHADAP KARAKTERISTIK KRIM - Susendiana Adi, I Kadek Alit; Mulyani, Sri; Harsojuwono, Bambang Admadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 3 (2019): September, 2019)
This research aims to : 1) know the  effect  of pH buffer and active ingredients of turmeric extrac, tamarind leaves extract and combination turmeric–tamarind leaves extract on the characteristics of the cream produced. 2) determine the pH buffer and active ingredients of turmeric extrac, tamarind leaves extract and combination turmeric–tamarind leaves extract which produce the best cream characterstics. The study used factorial pattern randomized block design. The first factor is the addition of a buffer of the three levels,  namely pH buffer 4, 5, 6. The second factor is the amount of turmeric exctrac, tamarind leaves extract, and mixied turmeric exctrac - tamarind leaves extract. The results of the study showed that the treatment of adding pH buffer had an effect on the pH of the cream, and did not affect the homogeneity of the cream, separation ratio, dispersion, viscosity, adhesion time, total phenolic. The addition of turmeric extract, tamarind leaves extract, and combination of turmeric-tamarind leaves extract had an effect on the pH of the cream and total phenolic acid, whereas it did not affect homogeneity, separation ratio, spreadability, viscosity, adhesion time. All cream formulations meet SNI, namely homogeneity cream characteristics, separation ratio =1, pH, dispersion time, and total phenolic cream, with the best formulation at pH 4 buffer and turmeric extract namely pH cream (6,68), power spread of cream (5,39) cm, cream viscosity (20,200) cp, cream sticky time (16.90) second, and total phenolic cream (10.83) mg GAE/g. Keywords : cream, pH buffer, turmeric extrac, thamarin leaves exctrac, and  combination turmeric-thamarin leaves extrac.